Prevalence and proposed mechanisms of chronic low back pain in baseball: part i - Wasser, J. G.; Zaremski, J. L.; Herman, D. C.; Vincent, H. K. (Research in Sports Medicine, 2017)
The prevalence of low back pain (LBP) among active baseball players ranges between 3 and 15%. The execution of baseball-specific manoeuvres, such as pitching or batting, may be related to the onset of LBP. These baseball motions are complex and require appropriate activation of the core musculature to produce a well-timed motion with forces minimized at the extremities. The spine, core and back musculature are involved with acceleration and deceleration of rotational motions. This narrative review synopsizes the available evidence of the prevalence of and mechanical factors underlying LBP in the baseball population. Possible mechanical mechanisms linking baseball play to LBP include aberrant motion, improper timing, high lumbar stress due to mechanical loading and lumbopelvic strength deficits. Potential clinical implications relating to these possible mechanical mechanisms will also be highlighted. The state of the evidence suggests that there are deficits in understanding the role of baseball motion and playing history in the development of spine conditions.